2014
DOI: 10.1111/mmi.12862
|View full text |Cite
|
Sign up to set email alerts
|

Specific N‐terminal cleavage of ribosomal protein L27 in Staphylococcus aureus and related bacteria

Abstract: Summary Ribosomal protein L27 is a component of the eubacterial large ribosomal subunit that has been shown to play a critical role in substrate stabilization during protein synthesis. This function is mediated by the L27 N-terminus, which protrudes into the peptidyl transferase center. In this report we demonstrate that L27 in Staphylococcus aureus and other Firmicutes is encoded with an N-terminal extension that is not present in most Gram-negative organisms, and is absent from mature ribosomes. We have iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 43 publications
4
49
0
Order By: Relevance
“…4E). It was recently reported that in S. aureus, bL27 has an extended N terminus that is cleaved posttranslationally after amino acid 9 by a specific essential protease, before or concurrent with ribosome assembly (44). In D50S, it reaches the acceptor stem of the P-site tRNA (40), whereas in T70S, it reaches the PTC and interacts with the CCA 3′ end of the P-site tRNA (6).…”
Section: Resultsmentioning
confidence: 99%
“…4E). It was recently reported that in S. aureus, bL27 has an extended N terminus that is cleaved posttranslationally after amino acid 9 by a specific essential protease, before or concurrent with ribosome assembly (44). In D50S, it reaches the acceptor stem of the P-site tRNA (40), whereas in T70S, it reaches the PTC and interacts with the CCA 3′ end of the P-site tRNA (6).…”
Section: Resultsmentioning
confidence: 99%
“…Other families include peptidases that are effective during infection, by degrading antibodies (C66, M26 and M64); the generation of inhibitory peptides such as microcins (C96), and toxins (C10, C25, M30, N6, U69 and some peptidases from C60 and M4); or the degradation of antibiotics (M6, M56). Peptidases from other families are required for processing of proteins: C39 for bacteriocins, C108 for ribosomal protein L27 [36]; M90 for regulatory proteins.…”
Section: Familymentioning
confidence: 99%
“…ERIC1_1c15570 was attributed to the cysteine protease Prp family. This family cleaves the N terminus extension of ribosomal subunit L27 in eubacteria (Wall et al 2015). ERIC1_1c21190 was attributed by InterPro to the type 2 phosphatidic acid phosphatases (PAP2) enzymes.…”
Section: Other Factorsmentioning
confidence: 99%